2018
DOI: 10.1080/21645515.2018.1446718
|View full text |Cite
|
Sign up to set email alerts
|

Trends in herpes zoster epidemiology in Germany based on primary care sentinel surveillance data, 2005–2016

Abstract: Herpes zoster (HZ) is caused by reactivation of the varicella-zoster-virus (VZV). Childhood varicella vaccination, as recommended in Germany in 2004, may reduce the risk of HZ in vaccinated children but also virus circulation and thus the booster possibility of latent infected persons. In this context we analyzed age-specific trends in HZ epidemiology in Germany using data on HZ-associated outpatient consultations in participating sentinel sites and HZ-associated cases in all hospitals since 2005. We analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
(32 reference statements)
0
10
0
4
Order By: Relevance
“…When it comes to patients between 10 and 19 years of age, while there was an increased risk observed in the period 2000-2006, in the following years, the increase in the HZ incidence not only seemed to reach a plateau, but also lower rates were observed in 2010 compared to 2006 in the United States [2]. Epidemiologic data from other countries, such as Germany, seem to be in accordance with the latter, demonstrating a decreasing trend in the incidence of HZ in 5 to 9 year olds from 2010 and onwards and in the 10 to 14 year olds after 2013 [5].…”
Section: Discussionmentioning
confidence: 71%
“…When it comes to patients between 10 and 19 years of age, while there was an increased risk observed in the period 2000-2006, in the following years, the increase in the HZ incidence not only seemed to reach a plateau, but also lower rates were observed in 2010 compared to 2006 in the United States [2]. Epidemiologic data from other countries, such as Germany, seem to be in accordance with the latter, demonstrating a decreasing trend in the incidence of HZ in 5 to 9 year olds from 2010 and onwards and in the 10 to 14 year olds after 2013 [5].…”
Section: Discussionmentioning
confidence: 71%
“…Herpes zoster (shingles): All reports agreed that the rate of herpes zoster markedly increases with age, and women were affected more frequently than men [6, 8, 13].…”
Section: Resultsmentioning
confidence: 99%
“…Herpes zoster (shingles): All reports agreed that the rate of herpes zoster markedly increases with age, and women were affected more frequently than men [6,8,13]. Age-standardized incidence, which was 166-600/100,000 and thus lower than the raw incidence rate, was calculated in two studies [6,8]. One study also reported mortality rates, which were 0.21/100,000 and increased with age to a value of 3.86/100,000 in persons aged over 90 [13].…”
Section: Viral Skin Diseasesmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, although the cases of HZ in children decreased significantly from 2010 to 2015 in Germany after the implementation of the same 2-dose schedule of VZV vaccines as in Japan in 2009, the incidence of HZ in adults dramatically increased in the same period. 7 …”
Section: Discussionmentioning
confidence: 99%